A comparative study of early childhood education and care national documents between China and Finland - Niu, Shuanghong Jenny; Malinen, Olli-Pekka; Ruokonen, Inkeri; Melasalmi, Anitta; Siklander, Signe; Wang, Xinghua; Zhang, Heyi; Hurme, Tarja-Riitta; Moilanen, Jaakko H.; Li, Xiaowei; Wang, Lijuan (Frontiers in Education, 2024)
Early childhood education and care (ECEC) serves as a crucial foundation for children's holistic growth and lifelong learning (OECD, 2021). Despite its significance, comparative analyses of leading ECEC documents across cultures remain limited. To address this gap, our study conducts a comparative analysis to identify key aspects and examine similarities and differences in national ECEC documents from China and Finland. Methodologically, we used a triangle of researchers from China and Finland. We employed qualitative content analysis to systematically identify, examine, and compare the key aspects in these two countries from the leading ECEC documents, i.e. the Chinese national ECEC guidelines and the Finnish ECEC national core curriculum.The findings reveal numerous similarities alongside notable differences. Both countries place a high value on ECEC, emphasizing principles that shape the learning environment and use diverse pedagogical methods. However, nuanced variations exist in the approaches. The Chinese documents feature more specific guidelines tailored to different age groups, accompanied by detailed pedagogical suggestions, while the Finnish national core curriculum offers general guidelines for all preschool age groups, complemented by the unique feature of individual development plans for each child. The findings have significant implications for policymakers, ECEC educators, and practitioners in international contexts. Future studies are needed to further explore the specific pedagogies in ECEC between these two nations and to analyze how the curriculum and educational guidelines are implemented in pedagogical practices.